From circumspection to centrality: prime ministers and the growth of analysis, co-ordination, management in the UK intelligence community. Issue 1 (2nd January 2021) - Aldrich, Richard J.; Cormac, Rory
ABSTRACT: We argue that British intelligence was transformed during the eleven years that Winston Churchill and Clement Attlee were in power. This change focused on the relationship between intelligence and Downing Street. Previous premiers were uninterested, naïve and inexperienced in their approach. When Churchill took office all this changed since he not only harnessed the power of intelligence but also oversaw the development of a central brain in the form of the joint assessment machinery. Yet it required Clement Attlee, with a rather different personality from Churchill, to complete the revolution. Together they not only developed the machinery used by successive prime ministers, they also trained Eden, Macmillan, and Douglas-Home in the transformative power of intelligence – changing the nature of the core executive in the process. Nevertheless, intelligence under each new administration increasingly reflects the character of the premier.